2015
DOI: 10.1044/2015_ajslp-14-0062
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Adults With Intellectual Disability Manual Signs Through Their Support Staff: A Key Word Signing Program

Abstract: The KWS program was successful and can be applied in similar clinical settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 44 publications
0
27
0
2
Order By: Relevance
“…When staff consistently provide augmented input, clients are also more inclined to generalize AAC/KWS skills to other settings (Dodd & Gorey, 2014;Schepis et al, 1982). In one study by Meuris, Maes, and Zink, (2015), 12 months after direct support staff had initiated KWS implementation in a group residential home for adults with intellectual disabilities, clients used significantly more KWS and their spoken language skills were reported to have improved.…”
Section: Staff Use Of Abstractigningmentioning
confidence: 93%
See 1 more Smart Citation
“…When staff consistently provide augmented input, clients are also more inclined to generalize AAC/KWS skills to other settings (Dodd & Gorey, 2014;Schepis et al, 1982). In one study by Meuris, Maes, and Zink, (2015), 12 months after direct support staff had initiated KWS implementation in a group residential home for adults with intellectual disabilities, clients used significantly more KWS and their spoken language skills were reported to have improved.…”
Section: Staff Use Of Abstractigningmentioning
confidence: 93%
“…In addition, direct support staff appear to exhibit considerable variability in their use of KWS. For example, in the study by Meuris et al (2015), staff produced 0-38 manual signs during a 5-min staff-client conversation; in a study by Rombouts, Maes, and Zink, (2016a), staff supported between 5% and 75% of their utterances with KWS during a 10-min staff-client conversation. In 73% of Flemish services for adults with intellectual disabilities where KWS was implemented, the majority of direct support staff could produce fewer than 10 manual signs, whereas most clients (67%) were estimated to produce more than 10 distinct manual signs (Meuris et al 2014).…”
Section: Staff Use Of Abstractigningmentioning
confidence: 97%
“…These findings suggest that caution must be exercised before concluding that problems with constituent order are due to language or cognitive impairment, rather than the communication environment in which individuals operate. Although Meuris et al (2015) claim that consistent use of KWS input will resolve the symmetry problem, they only looked at the number and frequency of signs used by staff and users of the service. However, when Assessing language skills key word signers 2/11/2016 9 considering how language can develop through KWS, it is the distribution of signs in the input which is relevant: sequential patterns;, the relationship between sign and speech, and which constituents are involved.…”
Section: Processes Underpinning Abstractigningmentioning
confidence: 99%
“…Teachers and direct support staff are frequent communication partners of individuals with intellectual disabilities and can play an important role in day‐to‐day AAC implementation (Smith & Connolly, ; Kent‐Walsh et al, ; Meuris et al, ). By using KWS, staff may clarify their communication and adapt their language level (Loncke et al, , ).…”
Section: Introductionmentioning
confidence: 99%
“…Kaiser & Wright, ; Dodd & Gorey, ). After direct support staff modelled and prompted KWS, individuals with intellectual disabilities increased their use of KWS (Schepis et al, ; Carter, ; Meuris et al, ). In cross‐sectional studies, a positive association was found between the use of manual signs by individuals with intellectual disabilities and staff (Grove & McDougall, ; Rombouts et al, ).…”
Section: Introductionmentioning
confidence: 99%